1998
DOI: 10.1159/000017026
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Monoamine Oxidase B Activity in Dementia

Abstract: Platelet monoamine oxidase B (MAO-B) activity has been found to increase significantly in demented patients. For the first time, a 4-year follow-up of platelet MAO-B activity and Mini-Mental State (MMS) was performed in patients with probable dementia of the Alzheimer type (DAT) and age-matched controls. MAO-B activity of DAT patients increased significantly 2 years after the beginning of the study as compared with controls and remained significantly higher for the entire period of the examinations (p < 0.0001… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…However, Mao-B was stable increased from the early stage (SA = 1.20; effect size 2.7 n = 3), through the middle stage (SA = 1.22; effect size 1.36; n = 3) all the way to late stage (SA 1.18; effect size 1; n = 28) of our AD sample and did not correlate with MMSE of included AD patients. Hence, our observations were in accordance with earlier findings which similarly showed no correlation between the decrease of MMSE and an increase in the level of platelet Mao-B activity [68,69]. However, these observations indicate that the increase of Mao-B may be at an early stage of the disease, and cognitive decline may also be a consequence of the elevated expression and activity of this enzyme in the brain.…”
Section: Discussionsupporting
confidence: 93%
“…However, Mao-B was stable increased from the early stage (SA = 1.20; effect size 2.7 n = 3), through the middle stage (SA = 1.22; effect size 1.36; n = 3) all the way to late stage (SA 1.18; effect size 1; n = 28) of our AD sample and did not correlate with MMSE of included AD patients. Hence, our observations were in accordance with earlier findings which similarly showed no correlation between the decrease of MMSE and an increase in the level of platelet Mao-B activity [68,69]. However, these observations indicate that the increase of Mao-B may be at an early stage of the disease, and cognitive decline may also be a consequence of the elevated expression and activity of this enzyme in the brain.…”
Section: Discussionsupporting
confidence: 93%
“…This was demonstrated by [ 11 C]-L-deprenyl using whole hemisphere autoradiography (38)(39)(40), epidemiology (41,42), morphology (43), as well as single-photon emission computed tomography (44). Such studies demonstrated that: i) MAO activity in platelets was significantly increased in patients with AD and acted as a marker of behavioral characteristics in dementia disorders (41,(45)(46)(47)(48); ii) there were early and persistent alterations in MAO-A and -B in the brains of patients with AD (49); iii) activated MAO led to cognitive dysfunction (50); iv) activated MAO destroyed cholinergic neurons and caused disorders of the cholinergic system (51); v) activated MAO contributed to the formation of amyloid plaques (13,14) and vi) activated MAO was associated with the formation of NFTs.…”
Section: Involvement Of Mao In Neurodegenerationmentioning
confidence: 99%
“…Although we could find an inhibition of MAO-B activity after soluble peptide treatment, it cannot be concluded that these oligomers might be neuroprotective. An increased MAO-B activity was found in senile plaques (Saura et al, 1997) and in platelets of AD patients (Gotz et al, 1998), therefore our results of enhanced MAO-B activity following treatment with aggregated while not with soluble Aβ 42 peptides, might indicate the involvement of the fibrillar structures of Aβ 42 in the oxidative stress cascade known to play an important role in AD (Grünblatt et al, 2005;Grünblatt et al, 2010).…”
Section: Discussionmentioning
confidence: 50%
“…(Zhao et al, 2009). MAO-B activity is significantly increased in AD patients (Gotz et al, 1998;Grünblatt et al, 2005) and inhibition of MAO-B has a neuroprotective effects for AD (reviewed in (Riederer et al, 2004).…”
Section: Introductionmentioning
confidence: 99%